Water footprints of irrigated crops in the Chirakchi Watershed, Uzbekistan - Abeyou, Abeyou; Akramkhanov, Akmal; Gafurov, Zafar (Frontiers Media, 2025)
The water footprint of crops (WFP) is crucial to understand how efficiently water is used in a farming system. This study evaluated the green and blue water footprints of selected crops in the Chirakchi Watershed, located in southern Uzbekistan. The sustainability of water use in the region’s agriculture is a growing concern due to its arid climate and increasing reliance on irrigation. Understanding the spatial and temporal dynamics of crop water use is essential for improving productivity and ensuring long-term water resource sustainability. The study evaluates the sustainability of water use in the region agricultural practices by integrating two biophysical simulation models, SWAT (Soil and Water Assessment Tool) and APEX (Agricultural Policy Environmental eXtender), to assess water consumption patterns of cotton, wheat, carrot, and potato between 2000 and 2023. The result of the study indicated a significant variation in water use among the selected crops, with cotton water use being the highest among the selected crops. The findings also revealed a declining trend in rainfall (green water) and increasing dependence on irrigation (blue water), particularly for cotton and wheat. This pattern highlights the water-intensive nature of the region's dominant cropping system. These trends are alarming, given the region's arid climate and increasing water scarcity driven by climate change. The study highlights the urgent need for improved irrigation efficiency and the adoption of water-saving practices, such as mulching or precision irrigation, to mitigate unsustainable water consumption. This research offers valuable insights into improving water productivity and can inform policy and management strategies in Uzbekistan's agricultural sector.